(untitled) (Historia, 2021)
When Gonarezhou was declared a game sanctuary in 1934, there followed concerted efforts to remove all people resident in the park-designated area. This was a process that gained traction from the mid-1950s and was only accomplished in 1968. This study interrogates the various responses of the Shangaan to their displacement from Gonarezhou National Park (GNP), a terrain they called home. Three case studies are used to illustrate the varied reactions. The forced removals are examined in the broader discourse of the history of colonial conquest, land alienation and African resistance to colonially-imposed projects. By interrogating archival sources, oral testimonies and secondary literature, the study contends that the Shangaan of south-eastern Zimbabwe put up stiff resistance to eviction from the land of their ancestors. It also notes that while literature on the history of national parks in Zimbabwe abounds, the subject of Shangaan eviction experiences has attracted limited academic scholarship. This article seeks to augment the knowledge on Shangaan contest for the control of the Gonarezhou terrain during the period from 1957 to 1968.